Allosteric modulation of the GTPase activity of a bacterial LRRK2 homolog by conformation-specific Nanobodies. Issue 7 (2nd April 2020) - Leemans, Margaux; Galicia, Christian; Deyaert, Egon; Daems, Elise; Krause, Linda; Paesmans, Jone; Pardon, Els; Steyaert, Jan; Kortholt, Arjan; Sobott, Frank; Klostermeier, Dagmar; Versées, Wim
Abstract : Mutations in the Parkinson's disease (PD)-associated protein leucine-rich repeat kinase 2 (LRRK2) commonly lead to a reduction of GTPase activity and increase in kinase activity. Therefore, strategies for drug development have mainly been focusing on the design of LRRK2 kinase inhibitors. We recently showed that the central RocCOR domains (Roc: Ras of complex proteins; COR: C-terminal of Roc) of a bacterial LRRK2 homolog cycle between a dimeric and monomeric form concomitant with GTP binding and hydrolysis. PD-associated mutations can slow down GTP hydrolysis by stabilizing the protein in its dimeric form. Here, we report the identification of two Nanobodies (NbRoco1 and NbRoco2 ) that bind the bacterial Roco protein (CtRoco) in a conformation-specific way, with a preference for the GTP-bound state. NbRoco1 considerably increases the GTP turnover rate of CtRoco and reverts the decrease in GTPase activity caused by a PD-analogous mutation. We show that NbRoco1 exerts its effect by allosterically interfering with the CtRoco dimer–monomer cycle through the destabilization of the dimeric form. Hence, we provide the first proof of principle that allosteric modulation of the RocCOR dimer–monomer cycle can alter its GTPase activity, which might present a potential novel strategy to overcome the effect of LRRK2 PD mutations.